Olimpiodoro sobre la retórica en el Gorgias: un ejemplo de filosofía como armonización - Jiménez, Marta (2025)
The aim of this paper is to study the interpretative strategies employed by Olympiodorus in his Commentary on Plato’s Gorgias, and defend the thesis that it is an example of a refined and complex philosophical hermeneutics. Rather than merely reproducing without critique Socrates’ proposal concerning rhetoric or distorting it to serve his own interests, Olympiodorus presents a philosophically sophisticated interpretation of the Socratic premises in light of the distinctions made by Socrates himself in the dialogue. Thus, he shows how Plato’s position is more coherent with his own stance than the theories of the Aristotelians and the Stoics. Although Olympiodorus seeks to show that there exists a form of oratory that can be considered a legitimate practice, his proposal does not amount to a mere biased defense of oratory, but rather constitutes an attempt to philosophically solve the tensions that arise from the Gorgias. He uses a dual strategy: on the one hand, he disentangles the concept of experience (empeiria) from the concept of adulation (kolakeia), and on the other hand, he acknowledges experiential practices as legitimate arts and forms of knowledge. This enables him to differentiate between various ways of practicing rhetoric and to create a space for rhetoric as a legitimate practice with a political and ethical purpose. Olympiodorus uses sophisticated philosophical methods to uncover harmony beneath the apparent disagreement and thus creates a space for the practice of rhetoric as a respected profession.